Pembudayaan Dan Pengembangan Al-Qur’an Melalui Ekstra Kurikuler Pada Fakultas Agama Institut Agama Islam Nurul Jadid Paiton Probolinggo - Ali, Nur (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
Ideally Muslim community and students used holy qur’an as guidance in daily activities comprehensively. They must be able to read and understand it well. Therefore, being culturally and Developing holy Qur’an at Islamic university cannot only be conducted partially but should becomprehensively namely; reading it well, memorizing and understanding it comprehensively, and also must be able to implemented the values of it in daily activities. To realize it, Islamic faculty of Islamic Institute of Nurul Jadid (FAI-IAINJ) conducted it through being culturally and Developing holy Qur’an through extra curricular.Key Word: Reading and memorizing Holy Qur’an, Understanding Holy Qur’an, Extra curricular